2008
DOI: 10.1590/s0103-50532008000500004
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxylation of a hederagenin derived saponin by a Xylareaceous fungus found in fruits of Sapindus saponaria

Abstract: Durante nossos estudos visando a obtenção de microorganismos endofíticos associados a plantas tropicais, um fungo do grupo Xylareaceae foi isolado das partes internas dos frutos de Sapindus saponaria. Os frutos de S. saponaria acumulam grande quantidade de saponinas triterpênicas e sesquiterpênicas. A saponinaarabinopiranosil-hederagenina foi isolada por métodos cromatográfios após saponificação do extrato bruto obtido dos frutos de S. saponaria e admistrada junto ao meio de cultivo usado para crescimento do f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 11 publications
2
10
0
Order By: Relevance
“…The structures were established by spectroscopic methods ( 1 H and 13 C NMR, HSQC, HMBC, and ESI/MS) and by comparing them with literature data [8,10]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structures were established by spectroscopic methods ( 1 H and 13 C NMR, HSQC, HMBC, and ESI/MS) and by comparing them with literature data [8,10]. …”
Section: Methodsmentioning
confidence: 99%
“…The fruit of Sapindus saponaria L. (Sapindaceae), a medium-sized tropical tree, is used by population as soap for washing clothes, and for curing ulcers, external wounds and inflammations [7]. Scientific works has shown antimicrobial activity [8-10], but has been little studied. In a recent study, members of our research group isolated and identified the principal constituents of the n-BuOH saponins, saponins (S1 and S2), and also an acyclic oligoglycoside.…”
Section: Introductionmentioning
confidence: 99%
“…The fruit of Sapindus saponaria L. (Sapindaceae), a medium-sized tropical tree found principally in America and India, has shown antimicrobial activity [2-4], but few studies have been carried out with this plant.…”
Section: Introductionmentioning
confidence: 99%
“…Species from the Sapindaceae family are known for their traditional medicinal use as diuretics, stimulants, expectorants, natural surfactants, sedatives, and vermifuges and for their use in the treatment of stomachaches and dermatitis in many parts of the world 3 . Sapindus saponaria L. (Sapindaceae), popularly known as "sabão-de-soldado" and "saboeiro", is a medium-sized deciduous tree that occurs in the tropics of the Americas and India, where the fruit is used as a soap and as a medicine against ulcers, scabies, joint pain, inflammation 4 , 5 , 6 , 7 and skin lesions caused by fungi 8 . Sapindus saponaria is a potential candidate for the treatment of candidiasis in vitro and in vivo 9 , 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%